ChemInform Abstract: Removal of the Pyridine Directing Group from α‐Substituted N‐(Pyridin‐2‐yl)piperidines Obtained via Directed Ru‐Catalyzed sp3 C—H Functionalization. Issue 10 (11th March 2014) - Maes, Bert U. W.; et al., et al.
Abstract The authors present two methods for the title transformation.